Common Species Maintain a Large Root Radial Extent and a Stable Resource Use Status in Soil-Limited Environments: A Case Study in Subtropical China - Ma, Xingyu; Chen, Hongsong; Nie, Yunpeng (Frontiers in Plant Science, 2020)
Coarse root systems provide a framework for water and nutrient absorption from the soil, and play an important role in plant survival in harsh environments. However, the adaptions of plant roots in soil-limited environments with low water storage capacity and nutrient content needs to be better understood. The adaptation strategies of two common plant species (a deciduous tree Platycarya longipes and an evergreen shrub Tirpitzia ovoidea) from two contrasting habitats (a shallow rocky soil and a nearby deep soil) in a karst region of subtropical China were compared and analyzed. Foliar nutrient concentrations, stoichiometry, stable carbon and oxygen isotopes were used to determine plant nutrient and water use status across these two habitats. Six indexes, including maximum root depth, maximum root radial extent, number of major roots and secondary roots, and tapering rate and curvature, were all investigated to characterize coarse root systems. Results show that both species exhibited similar nutrient and water use status in the two habitats that had contrasting water holding capacity and available nutrient content. On the other hand, although maximum root depths of the individual plants were not deeper than 33 cm, maximum radial extents were much larger when compared to rooting depths. Specifically, the ratio of radial extent to depth in the soil-limited habitat was approximately 6 and 1.5 times higher than that in the deep-soil habitat for the tree and shrub, respectively. Additionally, especially for the tree, a larger root radial extent was further accompanied by lower root tapering rate and bending levels. Our results provided evidence that plants growing in soil-limited environments maintain a stable resource use status along with large radially extended coarse root systems in humid karst regions like southwest China.